Peran dan Efektivitas Guru BK dalam Membantu Siswa di MAN 2 Karawang - Ilham Mukhtar Sya’bani; Intan Pratama Mukti; Muhamad Rizky Akbar; Muhamad Bambang Yudistira; Nur Aini Farida (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2025)
This study examines the role of Guidance and Counseling (BK) teachers in helping students face personal, social, academic, and career problems. Using qualitative descriptive methods through interviews, observations, and documentation, this study found that BK services were carried out routinely through classical guidance, group services, and individual counseling that focused on self-development, career exploration, bullying prevention, and exam readiness. The effectiveness of the service is also supported by a conducive BK environment and collaboration between subject teachers, parents, and external parties such as psychologists or related institutions. However, various obstacles are still found, such as a high ratio of counselors to students, changes in education policies that require rapid adaptation, limited support facilities, and generational differences between counselors and students that affect communication patterns. This research emphasizes the importance of improving the professionalism of BK teachers through continuous training and strengthening synergy between educators to realize effective, responsive, and oriented BK services that are oriented towards the development of students' character in a holistic and sustainable manner.